Tradition and Innovation in Old English Metre - Burns, Rachel A.; Pascual, Rafael J. (Medieval Media and Culture, 2022)
The importance of metrical analysis to the broad work of textual criticism and literary analysis cannot be overstated. In the thirty years since the publication of R. D. Fulk's A History of Old English Meter, metrical theory has been brought to bear on questions of poetic style, dating and literary history, linguistics and language history, editing practice, manuscript analysis and scribal practice. The essays in this collection include contributions from both new scholars and established metrists. They focus on the application of metrical study to literary criticism and manuscript studies, engaging with current debate and offering new perspectives on the crucial role of metre to Old English scholarship.